Pembelajaran Bahasa Arab Melalui Media Berita Digital Indonesia Alyaum Untuk Meningkatkan Literasi Arab–Indonesia Mahasiswa S3 - Ali Fathurrahman; Haniah Haniah; Amrah Kasim; Baiq Raudatussolihah (CV. SINAR HOWUHOWU, 2026)
The advancement of digital technology has shifted the paradigm of Arabic language learning from reliance on conventional resources to the use of digital media that offers greater authenticity and contextual relevance. One such medium is the Indonesian digital news portal “Indonesia Alyaum”, which presents various information about Indonesia in Modern Standard Arabic. This study aims to analyze the use of “Indonesia Alyaum” in enhancing the Arabic-Indonesian literacy of doctoral students in the Arabic Language Education program at UIN Alauddin Makassar. Employing a qualitative field research approach, the study gathered data through in-depth interviews, observation, and documentation. The data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña, comprising data reduction, data display, and conclusion drawing. The findings indicate that the use of “Indonesia Alyaum” improves students' ability to read contemporary Arabic texts, enriches their academic vocabulary, fosters critical literacy, and strengthens their skills in translating or transforming information between Arabic and Indonesian. Furthermore, the use of digital news media boosts learning motivation and student participation in the learning process. The study recommends integrating Arabic-language digital news media as an alternative learning resource in graduate-level Arabic language education.